2020
DOI: 10.5664/jcsm.8338
|View full text |Cite
|
Sign up to set email alerts
|

Doxepin in children and adolescents with symptoms of insomnia: a single-center experience

Abstract: Study Objectives: Pediatric insomnia is a widespread problem and especially difficult to manage in children with neurodevelopmental disorders. There are currently no US Food and Drug Administration-approved medications to use once first-line therapy fails. The objective of this study was to evaluate the efficacy and tolerability of doxepin in pediatric patients. Methods: This is a retrospective single-center chart review of children and adolescents (2-17 years of age) whose sleep failed to improve with behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Antidepressants are occasionally prescribed for the treatment of pediatric insomnia, given that some have sedative side effects. While the tricyclic antidepressant doxepin has been FDA approved in low doses for the treatment of insomnia in adults, there is no FDA approved antidepressant for pediatric insomnia (Shah et al, 2020). Nonetheless, trazodone is frequently utilized by clinicians for pediatric insomnia when comorbid with mood and anxiety disorders.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Antidepressants are occasionally prescribed for the treatment of pediatric insomnia, given that some have sedative side effects. While the tricyclic antidepressant doxepin has been FDA approved in low doses for the treatment of insomnia in adults, there is no FDA approved antidepressant for pediatric insomnia (Shah et al, 2020). Nonetheless, trazodone is frequently utilized by clinicians for pediatric insomnia when comorbid with mood and anxiety disorders.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Research on the use of TCAs for chronic migraine [39], insomnia [40,41], alcohol use disorder [42,43], and neuropathic corneal pain has been conducted with indications of therapeutic efficacy, though adverse effects remain a concern.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…An in silico study has found that mizolastine exhibits excellent binding affinities when docked against the SARS-CoV-2 protease M pro crystal structure [ 70 ].Doxepin, a H1 receptor antagonist, could prevent a SARS-CoV-2 spike pseudovirus from entering the ACE2-HEK293T cell with a reduced infection rate of 25.82% [ 71 ]. The antiviral effect of doxepin may rely on its inhibition of the reuptake of serotonin and norepinephrine [ 72 ], which needs to be further explored. Hydroxyzine, diphenhydramine, and azelastine were shown to exert direct antiviral activity on SARS-CoV-2 in a model in which lentivirus pseudotyped with the SARS-CoV-2 surface glycoprotein was used to infect ACE2-expressing HEK293 cells [ 73 ].…”
Section: Inhibition Of Sars-cov-2 By H1 Receptor Antagonistsmentioning
confidence: 99%